2017
DOI: 10.1002/ase.1724
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of extracurricular participation in dissection in a prosection‐based medical anatomy program

Abstract: The purpose of this study was to evaluate the extracurricular cadaveric dissection program available to medical students at an institution with a modern (time-compressed, student-centered, and prosection-based) approach to medical anatomy education. Quantitative (Likert-style questions) and qualitative data (thematic analysis of open-ended commentary) were collated from a survey of three medical student cohorts who had completed preclerkship. Perceived benefits of dissection included the hands-on learning styl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 53 publications
5
31
0
Order By: Relevance
“…The report, however, did not elaborate on hours of teaching in the anatomic sciences. Further, while two articles by Whelan et al give extremely detailed data on anatomy education in the University of Ottawa Medical Program and how the adoption of a compressed prosection‐based curriculum (Whelan et al, 2016) was enhanced by the extracurricular dissection (Whelan et al, 2018), these studies do not discuss the Canadian situation in general. Overall, combined North American and American‐specific data suggest a decrease in the role of anatomy in medical education (Collins et al, 1994) and a shift to a more integrated curriculum in both Canada and the United States (Kitzes et al, 2007; Kirsh and Aron, 2008; Wilkerson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The report, however, did not elaborate on hours of teaching in the anatomic sciences. Further, while two articles by Whelan et al give extremely detailed data on anatomy education in the University of Ottawa Medical Program and how the adoption of a compressed prosection‐based curriculum (Whelan et al, 2016) was enhanced by the extracurricular dissection (Whelan et al, 2018), these studies do not discuss the Canadian situation in general. Overall, combined North American and American‐specific data suggest a decrease in the role of anatomy in medical education (Collins et al, 1994) and a shift to a more integrated curriculum in both Canada and the United States (Kitzes et al, 2007; Kirsh and Aron, 2008; Wilkerson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Other research has concluded that dissection offers stronger benefits to anatomical knowledge development (Pizzimenti et al, 2016; Thompson and Marshall, 2020) and that many students consider it necessary for their learning (Mwachaka et al, 2016; Flack and Nicholson, 2018). Accordingly, there is still no clear consensus on which approach is optimal for human anatomy education (Winkelmann, 2007; Whelan et al, 2018; Wilson et al, 2018; Kinirons et al, 2019; Thompson and Marshall, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a final note to underscore the importance of sustainability, examples from the past decade have demonstrated that removal of cadaveric dissection from the curriculum is often transient and, for myriad reasons, has resulted in reinstatement of dissection or, otherwise, provisions that allow students an option of a dissection-based course (Rizzolo and Stewart, 2006;Azer and Eizenberg, 2007;Moxham and Plaisant, 2007;Ghosh, 2017;Pais et al, 2017;Eppler et al, 2018;Whelan et al, 2018). So, if cadaveric dissection is not sustained, it will likely be missed when it is gone.…”
Section: Discussionmentioning
confidence: 99%